Woman on Board and Firm Value: Mediation Role of Environmental Management System - Thamrin, Emelyn Hosni; Ng, Suwandi; Tanamal, Cherly E (Magister Akuntansi - Universitas Atma Jaya Makassar, 2025)
This study investigates the role of woman on board in increasing firm value through the environmental management system. The relationships between variables in this research are supported by stakeholder theory, agency theory and signal theory. This study uses secondary data. The population in this study are all non-financial companies that are published in the Indonesia Stock Exchange during the 2018-2022 period. The number of companies that meet the criteria is 116 companies with a total sample of 580 data units. The data analysis technique of this study uses path analysis. This study provides that woman on board have a positive and significant effect on environmental management system, environmental management system have a positive and significant effect on firm value, and environmental management system can mediate the effect of woman on board on firm value.